PACHYDERMODACTYLY IN A RHEUMATOLOGIST'S PRACTICE - I. A. Chikova; M. M. Kostik; E. V. Sinelnikova; M. F. Dubko; O. I. Krasnogorskaya; A. I. Imelbaev; R. N. Polozov; N. V. Buchinskaya; E. A. Isupova; E. V. Gaidar; O. V. Kalashnikova; R. A. Nasyrov; et al. (Научно-практическая ревматология)
Pachydermodactyly is a rare form of fibromatosis, which is characterized by an asymptomatic soft tissue enlargement around the proximal interphalangeal (PIP) joints of the hand. The etiology of the disease is unknown. Its possible triggers are recurrent minimal trauma, a habit or compulsive need to intertwine or rub the fingers. Spindle-shaped finger deformation with soft tissue thickening around the PIP joints mimics the clinical presentation of juvenile idiopathic arthritis (JIA). The distinctive features may be the absence of morning stiffness, contractures, pain, inflammatory and immunological changes in blood tests; however, it is the opinion of a number of authors that pachydermodactyly can be correctly diagnosed only after morphological examination. The paper gives the clinical manifestations of the disease and approaches to its diagnosis and differential diagnosis. It also describes the results of a retrospective study of 5 patients diagnosed as having pachydermodactyly. The final diagnosis was established after laboratory, instrumental, and morphological studies. Specific therapy has not been elaborated; however, by taking into account possible precipitating factors, excessive trauma of the affected finger bone should be avoided. The timely recognition of the disease allow to avoid administration of aggressive antirheumatic therapy required for JIA.